MR imaging features of Nipah encephalitis - Sarji, S.A.; Abdullah, B.J.; Goh, K.J.; Tan, C.T.; Wong, K.T. (American Roentgen Ray Society (ARRS), 2000)
OBJECTIVE. The newly discovered Nipah virus causes an acute febrile encephalitic illness in humans that is associated with a high mortality. The purpose of this study is to describe the MR imaging findings of Nipah encephalitis.